Analysis of Risk Factors for Severe Postpartum Hemorrhage - Yongxin Zhang; Jing Zhang; Kaihua Guo; Yanan Gao; Yu Zhu; Guohua Zhang (IMR Press, 2024)
Background: The purpose of this study is to outline the probable causes of severe postpartum hemorrhage (sPPH), summarize its risk factors, and present strategies for its prevention and treatment. Methods: This is a retrospective analysis of the medical records of 1824 patients that showed postpartum hemorrhage (PPH) during natural delivery and were admitted to the Fourth Hospital of Shijiazhuang between 1 January, 2014 and 31 December, 2018. The pairing method was used in this study. We collected and analyzed the clinical data after dividing the patients into two groups, a study group (showing sPPH) and a control group (showing non-severe PPH), with each having 912 patients. Risk prevention strategies are also discussed. Results: In the study group, the conditions such as previous history of cesarean section, placental diseases (marginal placenta previa, placenta accreta, central placenta previa and low-lying placenta), IVF-ET pregnancy, antepartum hemorrhage, and prepartum hemoglobin (g/L) were prevalent but rarely reported in the control group. The multivariate logistic regression results showed that BMI before pregnancy, past history of postpartum hemorrhage, prepartum APTT, prepartum fibrinogen (FIB) (g/L), pre-transfusion hemoglobin (g/L), pre-transfusion platelet count (×109), pre-transfusion coagulation function prothrombin time (PT), marginal placenta previa, placenta accreta, central placenta previa, IVF-ET pregnancy and antepartum hemorrhage were all independent risk factors for sPPH. Conclusions: Probable causes of sPPH related and risk factors in order to present prevention and treatment strategies in a retrospective analysis of 1824 patients that showed PPH were outlined. Since occurrence of sPPH has been related to these various factors, constructing a risk prevention strategy against these independent factors can effectively reduce the rate of maternal mortality.